Аналіз законодавчих вимог до якості шоколадних виробів - Романко, К. Є. (ХНУРЕ, 2025)
This work ensures the quality and safety of chocolate products for Ukrainian consumers and European growth. It examines key quality standards, regulatory requirements, and international norms. Special attention is given to compliance with national legislation and EU directives on ingredients, labeling, and food safety. Maintaining high product standards builds consumer trust, strengthens market positions, and creates export opportunities. Adhering to these requirements enhances the competitiveness of Ukrainian chocolate manufacturers and supports their integration into the global confectionery industry.
Keywords: аналіз законодавчих вимог; якість шоколадних виробів